Analisis Efektivitas Program One Pesantren One Product (OPOP) dalam Mendukung Pemberdayaan Ekonomi Pesantren di Kabupaten Belitung: Analysis of the Effectiveness of the One Pesantren One Product (OPOP) Program in Supporting the Economic Empowerment of Islamic Boarding Schools in Belitung Regency - Putra Pratama Saputra; Ryand Daddy Setyawan; Muhammad Kurnia (Society, 2023)
The One Pesantren One Product (OPOP) program aims to foster self-reliance within the community, including Islamic boarding schools, students, and the public. Its goal is to enable economic and social independence, enhancing skills, production technology, distribution, and marketing through innovative and strategic approaches. The program is designed to support Islamic boarding schools in achieving self-sufficiency and as a catalyst for tourism development in the region. Belitung Regency hosts several longstanding Islamic boarding schools, predating the establishment of the Bangka Belitung Islands Province. Through the OPOP Program, these institutions are envisioned to play a significant role in the region’s tourism development, contributing to economic growth. This research seeks to describe and analyze the effectiveness of the OPOP Program in supporting the economic empowerment of Islamic boarding schools in Belitung Regency. Conducted over a year, the research employs a descriptive qualitative method, utilizing purposive sampling techniques to select data sources, including Islamic boarding school administrators, teachers, and students. Data collection methods encompass interviews, observations, and documentary studies. The findings reveal that the Islamic boarding school cooperatives function as business units directly subordinate to the schools, akin to other commercial entities. Enhancement efforts are identified in marketing strategies, training initiatives, and internships. Media assistance and engagement with religious community organizations are essential for effective marketing. At the same time, collaboration with governmental and private sector entities is crucial for training and internship programs, ensuring alignment between participants’ business domains and their internship placements.